MANAJEMEN EVALUASI PROSES PEMBELAJARAN BAHASA INDONESIA DALAM MENINGKATKAN HASIL BELAJAR PESERTA DIDIK DI SMP NEGERI 2 SYAMTALIRA ARON - Rizki, Daini (LPPM Universitas Islam 45, 2025)
The process of delivering instruction, teaching, and training to students aims to achieve optimal learning outcomes. However, merely providing instructional material is insufficient to attain maximum learning results without being accompanied by effective learning management. This study was conducted with the purpose of describing the planning process prior to instruction, the implementation of instruction based on established learning standards, as well as the evaluation processes and forms employed to enhance student learning outcomes at SMP Negeri 2 Syamtalira Aron, particularly for Grade VIII students. This research focuses on the planning, implementation, and evaluation of the instructional process at SMP Negeri 2 Syamtalira Aron. The objective of the study is to explore the planning, implementation, and evaluation practices employed at the school. The research adopts a qualitative approach with a descriptive research design. Data collection techniques involved observation. The findings indicate that instructional planning at SMP Negeri 2 Syamtalira Aron has not been carried out effectively, as evidenced by the fact that the students' average scores have not yet met the established minimum mastery criteria (KKM).